Perceptions of research burden among participants in ADC cohorts: Epidemiology / Innovative methods in epidemiology (i.e., assessment methods, design, recruitment strategies, statistical methods, etc.). (7th December 2020) - Lingler, Jennifer; Coble, Dean W; Bollinger, Rebecca; Edwards, Dorothy Farrar; Gabel, Matthew; Grill, Josh D; Knox, Melissa; Stark, Susan
Abstract: Background: The burden of participating in research on Alzheimer's disease and related disorders (ADRD) has been described as extending beyond the direct risks associated with research procedures to encompass the overall hassle of getting to and through study visits. The Perceived Research Burden Assessment (PeRBA) was designed to measure participants' perceptions of the logistical (e.g., time commitment), psychological (e.g., intrusiveness of interview questions), and physical burden (e.g., perceived risk of injury) associated with enrollment in ADRD research. Initially validated using a pre‐enrollment version of PeRBA to assess the anticipated burden of a hypothetical research study, our team administered a post‐enrollment version of PeRBA to assess research burden as experienced by participants in longitudinal cohort studies of ADRD. Method: PeRBA interviews were administered by telephone to a random sample of 443 participants from the active cohorts at four NIA‐funded Alzheimer's Disease Centers (ADCs; n=∼110 per site). Survey respondents were on average 73 years old, primarily Caucasian (79%), female (59%), and had been participating in UDS study visits for 5 years. Respondents were instructed to reflect on their most recent UDS study visit as they considered each of the 22 PeRBA items. Principal component (unrotated) factor analysis was performed using STATA 15.0 to estimate the factor structure and confirm the PeRBA burden dimension based on eigenvalues and the pattern of factor loadings. Result: The factor analysis suggests a single factor solution, with PeRBA items loading constituent with a general perception of burden. Factor structure and fit were consistent across sites. Conclusion: These findings provide cross‐validation for prior research suggesting that the PeRBA is psychometrically valid measure of perceived research burden. Our finding of a single factor solution suggests that perceived research burden is a unidimensional construct and that use of the total PeRBA score is appropriate.